Pengaruh Pengaruh Komitmen Afektif Terhadap Kinerja Guru di Raudhatul Athfal Ashabulyamin - Aisyah, Ade; Zultiar, Indra; Ashshidiqi, Alfian (Tunas Siliwangi, 2024)
this study aims to determine how much influence affective commitment has on teacher performance at Raudhatul Athfal Ashabulyamin Cianjur. The type of research conducted in this study is the survey method. Data collection techniques by observation (questionnaire or questionnaire) and research results tend to be generalized. Technical data analysis using simple regression analysis. The research subjects for performance improvement were all educators or teachers at Raudhatul Athfal Ashabulyamin Cianjur totaling 14 people. The population of this study was 14 people and the sample of this study was 14 people. From the results of the research and the results of data analysis, it can be concluded that there is a significant regression or influence, namely the Pearson product moment correlation coefficient r = 0.829 with t count = 1.998 this value is greater than t table = 1.788 (t count value (1.998) > t table (1.788)), and the significance value is below 0.05. then Ha is accepted (regression is not significant) while Ho is rejected (significant regression) which means that there is a high or significant influence between the effect of affective commitment on teacher performance. That is, the higher the affective commitment, the higher the teacher performance obtained.